FEATURES OF LABOR IN AGRICULTURE - Kh.O.Qosimov (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Summary: The article outlines the main provisions of the system of "special assessment of working conditions", introduced instead of the previous certification of workplaces  in  the  agricultural  sector.  The  classification  of  working  conditions according to the degree of hazard used in the identification of workplaces is presented. The  experience  of  assessing  working  conditions  at  Joint-Stock  company  is reflected.They are especially susceptible to workers employed in fodder production, crop production and animal husbandry, who are constantly in contact with biological harmful substances of animal and plant origin (weed seeds, plant dust, wool, fluff, hair, feathers,  scales  skin,  claws,  hooves,  faecal  particles,  crude  protein  and  fat,  ether extractable substances, etc.)